Reputation: 17
I'm currently preparing for my final exam regarding Haskell, and I am going over the Monads and we were giving an example such as:
Given the following definition for the List Monad:
instance Monad [] where
m >>= f = concatMap f m
return x = [x]
where the types of (>>=)
and concatMap
are
(>>=) :: [a] -> (a -> [b]) -> [b]
concatMap :: (a -> [b]) -> [a] -> [b]
What is the result of the expression?
> [1,2,3] >>= \x -> [x..3] >>= \y -> return x
[1, 1, 1, 2, 2, 3] //Answer
Here the answer is different from what I thought it to be, now we briefly went over Monads, but from what I understand (>>=)
is called bind and could be read in the expression above as "applyMaybe". In this case for the first part of bind we get [1,2,3,2,3,3]
and we continue to the second part of the bind, but return x
is defined to return the list of x. Which should have been [1,2,3,2,3,3]
. However, I might have misunderstood the expression. Can anyone explain the wrong doing of my approach and how should I have tackled this. Thanks.
Upvotes: 1
Views: 113
Reputation: 34378
this case for the first part of bind we get [1,2,3,2,3,3]
Correct.
and we continue to the second part of the bind, but "return x" is defined to return the list of x. Which should have been [1,2,3,2,3,3].
Note that, in...
[1,2,3] >>= \x -> [x..3] >>= \y -> return x
... x
is bound by (the lambda of) the first (>>=)
, and not by the second one. Some extra parentheses might make that clearer:
[1,2,3] >>= (\x -> [x..3] >>= (\y -> return x))
In \y -> return x
, the values bound to y
(that is, the elements of [1,2,3,2,3,3]
) are ignored, and replaced by the corresponding values bound to x
(that is, the elements of the original list from which each y
was generated). Schematically, we have:
[1, 2, 3] -- [1,2,3]
[1,2,3, 2,3, 3] -- [1,2,3] >>= \x -> [x..3]
[1,1,1, 2,2, 3] -- [1,2,3] >>= \x -> [x..3] >>= \y -> return x
Upvotes: 2
Reputation: 120711
First, let's be clear how this expression is parsed: lambdas are syntactic heralds, i.e. they grab as much as they can to their right, using it as the function result. So what you have there is parsed as
[1,2,3] >>= (\x -> ([x..3] >>= \y -> return x))
The inner expression is actually written more complicated than it should be. y
isn't used at all, and a >>= \_ -> p
can just be written as a >> p
. There's an even better replacement though: generally, the monadic bind a >>= \q -> return (f q)
is equivalent to fmap f a
, so your expression should really be written
[1,2,3] >>= (\x -> (fmap (const x) [x..3]))
or
[1,2,3] >>= \x -> map (const x) [x..3]
or
[1,2,3] >>= \x -> replicate (3-x+1) x
At this point it should be pretty clear what the result will be, since >>=
in the list monad simply maps over each element and concatenates the results.
Upvotes: 1